Study of Chemical and Microbiological Composition of Kung-Som from Pak Phanang, Nakhon Si Thammarat Using Lactobacillus pentosus L35 as a Fermentation Starter การศึกษาองค์ประกอบทางเคมีและจุลชีววิทยาของกุ้งส้มปากพนัง จังหวัดนครศรีธรรมราช ที่ใช้ Lactobacillus pentosus L35 เป็นกล้าเชื้อในการหมัก - Thongsom, Montakarn (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2020)
Kung-Som from Pak Phanang is a local food that is popular for consumption and for its health benefits. The objective of this research was to study the chemical and microbiological compositions of the formula of traditional Kung-som and the formula of Kung-som produced by using Lactobacillus pentosus L35 as a fermentation starter. The results showed that L. pentosus L35, or lactic acid bacteria, had a stable growth for about 24 hours. The chemical compositions of traditional Kung-Som and Kung-Som produced by L. pentosus L35 as a starter were found significant differences (p > 0.05) in protein, ash, fat, salt, pH and total acid whereas the moisture was not. Microbial counts during fermentation were found that the total viable count increased at day 5 and decreased at the end of fermentation time (10 days). Total yeast and fungi slightly increased while lactic acid bacteria continually increased until day 10. The microbiological quality of results of Kung-Som showed that the numbers of pathogenic bacteria (Salmonella sp., Staphylococcus aureus, Bacillus cereus, Clostridium perfringens and Escherichia coli) did not exceed the Thai community product standard criteria for Kung-Som.